INDIKASI MANAJEMEN LABA PADA PERISTIWA PERGANTIAN CEO - , Priskila Adiasih, SE., Prof. Dr. Indra Wijaya Kusuma, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study proposes to investigate earnings management of CEO changes in Indonesia. Classification of CEO changes as routine or non-routine is based on RUPS (General Shareholders Meeting) and RUPSLB (Extraordinary General Shareholders Meeting) information. The samples are listed company undergoing CEO changes in the IDX observed from 2000 to 2009. The study provides evidence of non-routine incoming CEOs who undertakes earnings management by minimizing the earnings in the year of CEO change. The evidence shows that gaining minimum earnings is consistent with the notion of new CEOâs engagement in an âearnings bathâ. However, this study does not support the theory of management compensation contracts during CEO changes.